Passandra septentrionaria sp. nov.: the first described species of Passandridae (Coleoptera: Cucujoidea) from Eocene Baltic amber - Bukejs, Andris; Alekseev, Vitalii I.; Mckellar, Ryan C. (Zootaxa, 2016)
Based on two relatively well-preserved specimens from Eocene Baltic amber, Passandra septentrionaria sp. nov. is described and illustrated. It is the first formally described species of Passandridae from Baltic amber, and the first known European representative of the family. The global distribution of extant Passandra Dalman is mapped, and the historical distribution of the group is briefly discussed.